Sistem Informasi Manajemen Pemasaran Sebagai Strategi Peningkatan Penjualan Di Era Digital - Natasya, Anggi; Nasution, Muhammad Irwan Padli (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
This research aims to analyze the role of the Marketing Management Information System (SIMP) as a strategy to increase sales in the digital era. The development of information technology has changed the traditional marketing paradigm towards a data-based model, where decision making is driven by fast and accurate information analysis. Marketing information systems play an important role in integrating the processes of collecting, processing and presenting customer data to support the formulation of effective promotional and sales strategies. Proper implementation of SIMP can help organizations understand consumer behavior, predict market trends, and optimize distribution and customer service. Thus, marketing management information systems are a key component in creating business competitiveness in the competitive digital era.